A qualitative study on older primary care patients’ perspectives on depression and its treatments: potential barriers to and opportunities for managing depression - Stark, Anne; Weyerer, Siegfried (BMC family practice, 2018)
Background: Depression is one of the most common mental disorders in old age and is associated with various negative health consequences for the affected individual. Studies suggest that patients’ views on depression have an impact on help-seeking behaviour and treatment. It is thus important to investigate the patient’s perspective in order to ascertain optimum management of depression in late life. However, studies on depression and its treatment exploring the perspectives of primary care patients 75 years or older, are rare. Methods: Qualitative data was collected in semi-structured interviews with 12 primary care patients 75 years of age or older with symptoms of depression. Data was analysed using qualitative content analysis. Results: The study’s results show the multifaceted views on and treatment of depression in primary care patients 75 years of age or older. Some patients seemed well informed about depression and believed in the efficacy of different treatments, such as medications or psychotherapy. However, some individuals had misconceptions about depression and its treatments. Patients mentioned that they would rather avoid talking about depression within their social network, in part of fear of negative reactions. Furthermore, participants believed that other people had little understanding for people with depression. Patients had different views on the relevance of the general practitioner’s (GP) role in treating depression; some patients believed that the GP had little importance in the treatment of depression. Conclusions: This study identified positive views of primary care patients 75 years of age or older towards depression as well as views that might hinder optimal treatments. Exemplary implications for an improved management of depression are: educating older adults about depression via age-specific information and having professionals encourage patients in believing that depression is a recognised disorder.
Gesehen am 02.10.2019